2004
DOI: 10.1073/pnas.0405116101
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring H-DNA-forming sequences are mutagenic in mammalian cells

Abstract: Naturally occurring DNA sequences can form noncanonical structures such as H-DNA, which are abundant and regulate the expression of several disease-linked genes. Here, we show that H-DNAforming sequences are intrinsically mutagenic in mammalian cells. This finding suggests that DNA is a causative factor in mutagenesis and not just the end product. By using the endogenous H-DNAforming sequence found in the human c-myc promoter, mutation frequencies in a reporter gene were increased Ϸ20-fold over background in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
179
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(199 citation statements)
references
References 50 publications
13
179
0
Order By: Relevance
“…In Figure 5 we outline potential H-DNA-induced deletion or translocation pathways. Further, DSBs were found near the H-DNA locus on the plasmids recovered from mammalian cells [124]. Similarly, Bacolla et al (2004) found that the 2.5-kbp polypyrimidine sequence in the human PKD1 gene (as discussed above), induced DSBs at the regions that form H-DNA, and resulted in large-scale deletions in E. coli [128].…”
Section: Detecting H-dna In Vitro and In Vivomentioning
confidence: 84%
See 1 more Smart Citation
“…In Figure 5 we outline potential H-DNA-induced deletion or translocation pathways. Further, DSBs were found near the H-DNA locus on the plasmids recovered from mammalian cells [124]. Similarly, Bacolla et al (2004) found that the 2.5-kbp polypyrimidine sequence in the human PKD1 gene (as discussed above), induced DSBs at the regions that form H-DNA, and resulted in large-scale deletions in E. coli [128].…”
Section: Detecting H-dna In Vitro and In Vivomentioning
confidence: 84%
“…In addition to the truncation and missense mutations, further analysis revealed complex germ line rearrangements in a 5.8 kb fragment harboring the polypyrimidine tracts of introns 21 and 22 in patients [123]. We have demonstrated that H-DNA structures are intrinsically mutagenic in mammalian cells [124]. Either the endogenous H-DNA-forming sequence from the human c-MYC promoter where a breakpoint hotspot is found in diseases such as Burkitt's lymphoma [125][126][127], or model H-DNA-forming sequences, induced mutation frequencies ~20-fold above background levels in a supF reporter gene in COS-7 cells.…”
Section: Detecting H-dna In Vitro and In Vivomentioning
confidence: 87%
“…4). As reported previously, deletion of the 201-bp c-myc DUE domain (⌬DUE) eliminated the origin activity of the wild type c-myc replicator (WT) (50), quantitated as relative nascent strand abundance, whereas previous work has shown that heterologous DUEs comprising expanded (ATTCT) 27 or (ATTCT) 48 pentanucleotide repeats from the ATXN10/SCA10 locus could function as DUEs and restore ectopic origin activity (39). However, replacement of the c-myc DUE with the IVS21 Pu-Py repeat in either orientation did not restore origin activity to a level greater than that at an unoccupied FRT site or at the FRT site occupied by non-origin control sequences (49,50).…”
Section: Alternative Dna Structures Formed By the Ivs21 Pu-pymentioning
confidence: 82%
“…Further evidence for in vivo effects of alternative DNA structures comes from model studies of the region between the P1 and P2 promoters of the human c-myc gene, which contains an asymmetric Pu-Py tract that can form triplex and G-quadruplex DNA (46). Mutations that destabilize the G-quadruplex enhanced c-myc-driven transcription in transient luciferase plasmid reporter assays (47), whereas mutations that enhanced triplex formation increased the frequency of mutation during plasmid replication assays (48).…”
mentioning
confidence: 99%
“…As with Z-DNA, the repeating sequence motif of H-DNA appears to be a source of genetic instability resulting from double-strand breaks. Wang and Vasquez (2004) reported a ~20 fold increase in mutation frequency upon incorporation of an H-DNA forming sequence found in the c-myc promoter region into mammalian cells. These results suggest that naturally occurring DNA sequences can cause increased mutagenesis via non-standard DNA structure formation.…”
Section: H-dna: Three's a Crowdmentioning
confidence: 99%